Ödeme – Kardinalsymptom des nephrotischen Syndroms - Kühne, Lucas; Brinkkötter, Paul Thomas (DMW - Deutsche Medizinische Wochenschrift, 2019)
Edema is a common symptom with mostly extrarenal causes. Nevertheless, it may also be a sign of glomerular disease. So renal causes should always be clarified to avoid serious complications, such as renal insufficiency, cardiovascular or thrombembolic events. The determination of the albumin-creatinine ratio in spot urine is easy to perform and the method of choice to diagnose nephrotic-range proteinuria. Renal biopsy then usually allows the definitive assignement to either glomerular or systemic disease. Salt restriction in combination with diuretics and antiproteinuric treatment are essential for an effective therapy. Depending on the underlying disease and individual risk factors, anticoagulation should also be considered.
Keywords: nephrotisches Syndrom; Proteinurie; Ödeme